Pengaruh Lingkungan Kerja dan Budaya Organisasi terhadap Motivasi Kerja Karyawan : (Studi Kasus: PDAM Tirta Kencana Kota Samarinda) - Annisa Adinda Azzahra Fatmawati; Asmadhini Handayani Rahmah; Hudyah Astuti Sudirman (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee work motivation is an important factor in increasing productivity and achieving organizational goals, which can be influenced by a pleasant work environment and a strong organizational culture. This study aims to determine the work environment and organizational culture on the work motivation of employees of PDAM Tirta Kencana, Samarinda City. This study uses a quantitative approach with an associative method. Data collection was carried out by distributing questionnaires in the form of Google Forms to respondents who are permanent employees of PDAM Tirta Kencana, Samarinda City. The study population was 412 respondents and the sample was determined as many as 203 respondents using a purposive sampling technique. Data were analyzed using instrument testing, classical acceptance testing, multiple linear regression testing and hypothesis testing. The results of the study showed that: (i) the work environment has a positive and significant effect on employee work motivation, (ii) organizational culture has a positive and significant effect on employee work motivation, and (iii) both independent variables, namely the work environment and organizational culture simultaneously have a positive and significant effect on employee work motivation. These results indicate that companies need to create a conducive work environment and build a healthy organizational culture in order to increase employee work motivation sustainably.